What Are the Challenges of AI in Pharmaceutical Research? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Artificial intelligence (AI) is poised to revolutionize the pharmaceutical industry, promising to accelerate drug discovery, streamline clinical trials, and ...
Keywords: Drug Discovery and Pharmaceutical AI; Challenges; Pharmaceutical; Research; Artificial Intelligence; Machine Learning; Deep Learning